2006
DOI: 10.1534/genetics.105.049072
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Silencing and Functional Characterization of theDrosophila melanogasterHomolog of HumanSurf1

Abstract: Mutations in Surf1, a human gene involved in the assembly of cytochrome c oxidase (COX), cause Leigh syndrome, the most common infantile mitochondrial encephalopathy, characterized by a specific COX deficiency. We report the generation and characterization of functional knockdown (KD) lines for Surf1 in Drosophila. KD was produced by post-transcriptional silencing employing a transgene encoding a dsRNA fragment of the Drosophila homolog of human Surf1, activated by the UAS transcriptional activator. Two altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 46 publications
(39 reference statements)
1
40
0
Order By: Relevance
“…Accordingly, the total amount of ATP in RNAiB2 larvae was maintained at 70% of control larvae, such that the defect in mitochondrial synthetic capacity is largely compensated by glycolysis. Furthermore, we found that RNAiB2 larvae exhibit a substantial increase in the activity of citrate synthase and complex II activities, and in the steadystate level of hsp60, which are considered to be markers of mitochondrial mass (33). We interpret these findings to suggest that OXPHOS impairment due to a reduced amount of TFB2M induces a compensatory response that increases mitochondrial mass.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Accordingly, the total amount of ATP in RNAiB2 larvae was maintained at 70% of control larvae, such that the defect in mitochondrial synthetic capacity is largely compensated by glycolysis. Furthermore, we found that RNAiB2 larvae exhibit a substantial increase in the activity of citrate synthase and complex II activities, and in the steadystate level of hsp60, which are considered to be markers of mitochondrial mass (33). We interpret these findings to suggest that OXPHOS impairment due to a reduced amount of TFB2M induces a compensatory response that increases mitochondrial mass.…”
Section: Discussionmentioning
confidence: 63%
“…RNAi-dependent knockdown was induced using the da-GAL4 strain as a driver, which expresses the yeast transcriptional activator GAL4 under control of the daughterless enhancer. da-GAL4 expresses GAL4 throughout development and in most if not all tissues, and has been used extensively to overexpress constitutively transgenes containing UAS binding sites in Drosophila (33).…”
Section: D-tfb2m Is Essential During Drosophila Development-to Characmentioning
confidence: 99%
“…The walking optomotor test was performed as in ref. 52 (setup 1 in SI Materials and Methods). Details of setups 1 and 2 are given in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Agostino et al (2003) have generated a Surf1 knockout mouse model of Leigh syndrome that lacks Surfeit-1, an enzyme involved in COX assembly. Similarly, a Surf1 knockdown model has been generated in Drosophila by post-transcriptional silencing using dsRNA (Zordan et al 2006). Studies comparing biochemical and physiological characteristics of various models of COXrelated mitochondrial encephalomyopathies, including levy mutants and Surf1 models in mice and Drosophila, can help in understanding the mechanisms underlying the effects of such disorders.…”
Section: /Levymentioning
confidence: 99%